Multi-product firms and product quality - Manova, Kalina; Yu, Zhihong (Elsevier, 2017)
We examine the global operations of multi-product firms. We present a flexible heterogeneous firm trade model with either limited or strong scope for quality differentiation. Using customs data for China during 2002-2006, we empirically establish that firms allocate activity across products in line with a product hierarchy based on quality. Firms vary output quality across their products by using inputs of different quality levels. Their core competence is in varieties of superior quality that command higher prices but nevertheless generate higher sales. In markets where they offer fewer products, firms concentrate on their core varieties by dropping low-quality peripheral goods on the extensive margin and by shifting sales towards top-quality products on the intensive margin. The product quality ladder also governs firms’ export dynamics, both in general and in response to the exogenous removal of MFA quotas on textiles and apparel. Our results inform the drivers and measurement of firm performance, the effects of trade reforms, and the design of development policies.